Strategi Efektif dalam Meningkatkan Minat Baca Siswa di Sekolah Dasar - Abidah Putri Ardelia; Adrias Adrias; Salmaini Safitri Syam (Universitas 45 Surabaya, 2025)
Reading interest is a very important skill in the world of education, especially at the elementary school level. Optimal reading skills not only help students understand academic material but also develop critical and analytical thinking skills. However, the reality in the field shows that many elementary school students have low reading interest. Various internal and external factors influence the low reading interest. This study uses the Systematic Literature Review (SLR) method which is used to prepare this study by utilizing ideas in the Literature review by reviewing up to 10 journal articles published between 2022-2025. This approach is used to identify and analyze various strategies that have been implemented in increasing elementary school students' reading interest. With the implementation of the right strategy and support from various parties, it is hoped that students can develop reading habits from an early age.